ASSESSING ROLE OF SMALL BUSINESSES IN INCREASING PER CAPITA REAL INCOME IN KHORESM REGION - Ataev , Jaxongir (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
In this paper developed models for assessing role of small business entities in increasing real incomes of population in Khorezm region. Based on the results of the model, determined an elasticity coefficient, which reflects impact of changes in small business entities on real incomes of population.